A SUN POSITION DIAGRAM FOR PT. BARROW, ALASKA - BROWN,D.E. (1961)
A diagram was developed which gives continuously, all sun positions for Point Barrow, Alaska (71 deg 26 min n,) above, near, and below the horizon for Local Civil Time. No calculations are required. Instructions for use are included on the diagram. (Author)